2022
DOI: 10.3389/fphys.2021.798068
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Combination Intervention to Improve Physical Performance Among the Elderly: A Systematic Review

Abstract: The benefits of aerobic exercise for the elderly are well-known. They extend beyond cardiovascular changes and can reduce the inactivity-induced loss of strength, mobility, balance, and endurance that are vital for the safe performance of daily activities in older adults. However, the benefits of combined aerobic exercise with other exercises such as strength/resistance, multi-component and aerobic exercise remain unknown. The purpose of this study is to examine the effects of combined aerobic exercise on phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 57 publications
(338 reference statements)
1
17
0
Order By: Relevance
“…Furthermore, as already mentioned, in adolescents good cardiorespiratory fitness is positively related to body composition and metabolic syndrome in children and adolescents aged 5–19 years old [ 56 ]. Furthermore, low aerobic fitness carries negative consequences for the physical function in all age groups, such as increased metabolic and cardiac disease [ 57 , 58 ] and, in this sense, reveals the importance of keeping physically active in adolescence [ 59 , 60 , 61 ]. Additionally, keeping satisfactory aerobic fitness levels across the years is inversely related with all causes of mortality, such as cardiovascular disease, cancer, chronic lower respiratory tract diseases, accidents and injuries, Alzheimer’s disease, diabetes mellitus, influenza/pneumonia, nephritis, nephrotic syndrome, or nephrosis [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as already mentioned, in adolescents good cardiorespiratory fitness is positively related to body composition and metabolic syndrome in children and adolescents aged 5–19 years old [ 56 ]. Furthermore, low aerobic fitness carries negative consequences for the physical function in all age groups, such as increased metabolic and cardiac disease [ 57 , 58 ] and, in this sense, reveals the importance of keeping physically active in adolescence [ 59 , 60 , 61 ]. Additionally, keeping satisfactory aerobic fitness levels across the years is inversely related with all causes of mortality, such as cardiovascular disease, cancer, chronic lower respiratory tract diseases, accidents and injuries, Alzheimer’s disease, diabetes mellitus, influenza/pneumonia, nephritis, nephrotic syndrome, or nephrosis [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that muscle mass, muscle strength, and body fat was associated with the ability to perform ADL and IADL in older adults [4,5,6] . Moreover, reports have suggested that AE and RE improve physical performance, which has been associated with the ability to perform of ADL and IADL in older adults [4,8,9,10] .…”
Section: The Recommendation Of Ae and Re For Older Adultsmentioning
confidence: 99%
“…Resistance exercise (RE) and aerobic exercise (AE) have been shown to increase muscle mass and decrease body fat in older adults [7] , as well as improve physical performance, which has been associated with ADL and IADL capacity [4,8,9,10] . However, some older adults cannot tolerate formal or prolonged exercise, particularly older adults requiring care (in longterm care) due to conditions such as decreased exercise tolerance or pain.…”
Section: Introductionmentioning
confidence: 99%
“…We prescribed moderate-intensity aerobic exercise, meaning participants could talk but could not sing during the training period [16]. A recent systematic review of exercise intervention improving physical performance in the elderly reported that intervention times ranged from 4 to 52 weeks [17]. We chose the eight-week exercise program due to the practicality of conducting the multi-site project.…”
Section: Interventionmentioning
confidence: 99%